Pleiotropic effects of statins in stroke prevention - Yenny, Yenny (Faculty of Medicine, Trisakti University, 2009)
Cardiovascular disease is the leading cause of death and disability, andÂ contributes substantially to healthcare budgets. The lipid-lowering drugs, 3-hydroxy-3-methylgulutaryl-coenzyme A (HMG-CoA) reductase inhibitor or statins, reducing mortality and cardiovascular morbidity in patients with established cardiovascular disease. Statins therefore have a place in the secondary prevention of cardiovascular disease. Recent experimental and clinical studies suggest that statins may exert vascular protective effect beyond cholesterol reduction. The cholesterol-independet or â€œpleiotropicâ€ effects of statin include the upregulation and activation of endothelial nitric acid synthase (eNOS) that can increase nitric oxide (NO) production. Augmentation of NO production increases cerebral blood flow, which can lead to neuroprotection during brain ischaemia. By inhibiting mevalonate synthesis, statins prevent the formation of several isoprenoids (including farnesylpyrophosphate and geranylgeranylpyrophosphate). Inhibiting geranylgeranylation of RhoA small G proteins increases the stability of eNOS mRNA through the remodeling of endothelial actin microfilamens. Moreover, statins directly increase eNOS activity within minutes by activating the pathway involving phosphoinositide 3-kinase and protein kinase B. In the secondary prevention of stroke, the use of statins reduces the incidence of either recurrent stroke or other major vascular events and treatment should be initiated soon after the event. The use of statins does not increase hemorrhagic stroke or cancer and may also favor atherosclerotic plaque regression.